2011
DOI: 10.4021/jocmr738w
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Uncoupling Protein-1 Gene A-3826G Polymorphism and High-density Lipoprotein Cholesterol in A General Japanese Population: A Consideration of the Obesity Status

Abstract: BackgroundLimited studies have shown inconsistent data about the association between the uncoupling protein 1 (UCP1) gene A-3826G polymorphism and high-density lipoprotein (HDL) cholesterol levels. The present study investigated the association between the A-3826G polymorphism and low HDL-cholesterolemia in non-obese and obese subjects.MethodsAnthropometric and biochemical factors, in addition to genotyping by an allele-specific DNA assay, were measured in 294 community-dwelling Japanese subjects (male/female:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Kotani et al reported that the UCP1 -3826A > G polymorphism was associated with low HDL-cholesterolemia in obese Japanese patients [ 32 ]. In the current study we are unable to find a similar effect in overweight/obese subjects (OR = 1.296, CI = 0.743-2.261, P = 0.360), suggesting that UCP1 gene variation might not predispose overweight/obese Chinese subjects to the development of low HDL-cholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Kotani et al reported that the UCP1 -3826A > G polymorphism was associated with low HDL-cholesterolemia in obese Japanese patients [ 32 ]. In the current study we are unable to find a similar effect in overweight/obese subjects (OR = 1.296, CI = 0.743-2.261, P = 0.360), suggesting that UCP1 gene variation might not predispose overweight/obese Chinese subjects to the development of low HDL-cholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this mechanism to control blood lipids may be affected by genetic polymorphisms such as A-3826G polymorphism of UCP-1 gene [27]. This was proved by a study that showed lowered activation of sympathetic nerve and declined expression of UCP-1 in BAT of obese rats and by another in vivo study that reported overexpression of UCP-1 reduced degree of obesity induced by high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…The HDL played an antioxidant role [ 38 ], and the HDL levels were positively correlated with obesity status [ 39 , 40 ]. Moreover, Sestrin2 regulated the PERK-c/EBPβ pathway by mediating mTORCI [ 41 , 42 ], and inhibited the ROS-mediated p38 MAPK activation and interfered the expression of uncoupling protein 1 (Ucp1), subsequently resulting in the decrease of heat production and the increase of adipose tissue, which led to obesity [ 43 , 44 ]. In addition, HDL was reduced in inflammatory conditions [ 45 ], while Sestrin2 could inhibit TLR-mediated inflammatory responses in macrophages [ 46 ].…”
Section: Discussionmentioning
confidence: 99%